1985
DOI: 10.1056/nejm198502143120701
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Cardiac Risk by Dipyridamole-Thallium Imaging before Peripheral Vascular Surgery

Abstract: To evaluate the severity of coronary artery disease in patients with severe peripheral vascular disease requiring operation, we performed preoperative dipyridamole-thallium imaging in 54 stable patients with suspected coronary artery disease. Of the 54 patients, 48 had peripheral vascular surgery as scheduled without coronary angiography, of whom 8 (17 per cent) had postoperative cardiac ischemic events. The occurrence of these eight cardiac events could not have been predicted preoperatively by any clinical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
2

Year Published

1985
1985
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 658 publications
(74 citation statements)
references
References 19 publications
1
71
0
2
Order By: Relevance
“…Many algorithms have been proposed combining clinical risk indices, [13][14][15][16][17][18] exercise treadmill testing (ETT), [19][20][21] ambulatory electrocardiography (Holter monitoring), [22][23][24][25] radionuclide ventriculography (RNVG), 26,27 dipyridamole thallium scintigraphy (DTS), [28][29][30][31][32] dobutamine stress echocardiography, 33,34 and coronary angiography. 35,36 This vast array of tests and the multiple proposals for employing them indicates the absence of a consensus on the optimal approach for risk stratification in patients with peripheral arterial disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many algorithms have been proposed combining clinical risk indices, [13][14][15][16][17][18] exercise treadmill testing (ETT), [19][20][21] ambulatory electrocardiography (Holter monitoring), [22][23][24][25] radionuclide ventriculography (RNVG), 26,27 dipyridamole thallium scintigraphy (DTS), [28][29][30][31][32] dobutamine stress echocardiography, 33,34 and coronary angiography. 35,36 This vast array of tests and the multiple proposals for employing them indicates the absence of a consensus on the optimal approach for risk stratification in patients with peripheral arterial disease.…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30][31] In 1964, DeBakey and et al reported a 9% 30-day mortality in 1719 patients undergoing AAA repair, with most of the deaths being due to cardiac events, although it should be noted that this study also included patients with ruptured AAA. 28 In 1974, Thompson et al noted a 5.5% operative mortality in 108 patients undergoing AAA repair, with five of six deaths resulting from heart-related causes. 29 In 1990, Johnston et al, in a prospective study of 666 patients undergoing AAA repair reported an operative mortality rate of 4.8% and cardiac related mortality of 3.3%.…”
Section: Cardiac Mortality Following Aortic Reconstructionmentioning
confidence: 99%
“…2). [23][24][25][26][27][28][29][30][31][32][33][34] Thc pooled data for dipyridamole myocardial perfusion imaging reveal a positive and negative predictive value of 36 f: 1 1 % and 07 i 2%, respectively. The positive predictive value of a severe defect, defined as a multisegmental, reversible defect or a combination of fixed and reversible defect for cardiac events was 45 * 5% and is associated with an increased incidence of postoperative death and myocardial infarction.…”
Section: Stms -Myocardial Perfusion Imaging In Assessing Preoperativementioning
confidence: 94%
“…Although the incidence of coronary calcifications is high in patients with ESRD (682,683) Most data on the effectiveness of non-invasive screening techniques are from studies examining either dipyridamole thallium/sestamibi scintigraphy or dobutamine echocardiography. In non-ESRD patients, dipyridamole thallium/sestamibi scintigraphy has been reported to be useful in assessing cardiac risk before major surgery (669)(670)(671)(672)684). More recent data indicate that the routine use of thallium scintigraphy adds little to clinical data in defining surgical cardiac risk (658,674,685).…”
Section: Cardiovascular Diseasementioning
confidence: 99%